Ruminative tendencies in university students: the role of executive control in rumination and academic procrastination - Sousa, Mariana Sofia Ferreira de (2021)
Procrastination has been reported as a prevalent problem among university students. This phenomenon can be defined as a tendency to voluntarily postpone academic tasks regardless of the consequences that may come. Several studies indicate that procrastination is associated with deficits in executive control, as well as with self-critical and brooding ruminative tendencies. However, research on interventions that target these specific associations for reducing academic procrastination is scarce. In this sense, the present study aimed to explore the effectiveness of a cognitive training that associates executive control activation with exposure to procrastinatory content to reduce the tendency to procrastinate and ruminate. A sample of 79 university students (20 males, 59 females) was randomly assigned to one of two training conditions: experimental group (executive control activation mainly followed by the presentation of procrastinatory cognitions) and control group (executive control activation mainly followed by neutral cognitions). Participants performed a training task, and rated their state procrastination, brooding and self-critical rumination pre and post training. As expected, participants in the experimental group showed a greater reduction in state procrastination compared to the control group. The results found suggest that training individuals to recruit executive control while being exposed to procrastination stimuli can reduce academic procrastination. Although this is an exploratory study, and further studies are needed to validate the effectiveness of training, the promising results may have interesting implications for clinical and therapeutic strategies focused on automatic thoughts associated with academic procrastination.